PHOTOSYNTHESIS OF THE NEW DERIVATIVES 1,4-DIOXANONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
By interaction of 2-oxo-3-aIkhyl-6-substituted-l,4-dioxans with 2-oxo-3-alkhyl-6-methyl-l,4-hexacyclo-5-ens in the presence of catalytic quantities of zyncum chloride by laser radiation and room temperature dioxanonildioxanons are obtained with high yields. It has been studied the influence of c on the reaction yields.
Keywords: 2-oxo-3-aIkhyl-6-substituted-l,4-dioxans; 2-oxo-3-alkhyl-6-methyl-l,4-hexacyclo-5-ens; zyncum chloride; laser radiation; electroaceptoric substitute